Efektivitas Layanan Konseling Individu Dengan Pendekatan Realitas Untuk Pemantapan Peminatan Pada Peserta Didik SMAN-2 Palangkaraya: Effectiveness Of Individual Counseling Service Approach To Reality For Consolidation Of Learners Specialization SMAN 2 Palangkaraya - Fatmawati Fatmawati; Karyanti Karyanti (Suluh: Jurnal Bimbingan dan Konseling, 2018)
The purpose of this study is to find out the individual counselling services of SBMT and OAP can strengthen the interest of students of class XI MIPA at SMAN-2 Palangka Raya. The population in this study amounted to 35 students. The number of research samples consisted of 2 students. Sampling is determined by purposive sampling technique. The data collection technique uses observation and the scale of stabilisation of the audience. The method used is pre-experiment, the process of analysing data using One-Sample T-Test or better known as Pre-Post Design is an analysis involving two measurements on the same subject against a particular influence or treatment. Based on the results of the study and discussion above, it can be concluded that WDEP Individual Counseling Services (Wants, Direction, Evaluation, Plan) WDEP can strengthen specialisation in Students in Class XI MIPA 3 of SMAN-2 Palangka Raya. This is based on the results of the One-Sample T-Test, indicating that consolidation of speciality has increased by an average of 45 to 74, with an average number of increases of 29. Meaning "Counseling Services Individual Realities with Techniques (Wants, Direction, Evaluation, Plan) WDEP can improve stabilisation of interest in Class XI MIPA 3 Students of SMAN-2 Palangka Raya.